2019
DOI: 10.1055/s-0038-1677534
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Correlates for the Treatment of Ulnocarpal Impaction

Abstract: Background Ulnocarpal impaction (UCI) is a described cause of ulnar side wrist pain. Questions Does absolute ulnar variance (UV) or change in UV with grip affect patient-rated outcome scores (PROS) in patients with symptomatic UCI undergoing surgery? Does UV differ between symptomatic and contralateral wrists? Does arthroscopic grade of triangular fibrocartilaginous complex (TFCC) tears and lunotriquetral (LT) ligament tears influence PROS? Do PROS improve following ulnar shortening osteotomy (USO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…3 A study on ulnocarpal impaction found no difference in static ulnar variance between the symptomatic and contralateral wrist. 19 Static ulnar variance had no influence on the clinical results in our sample.…”
Section: Discussionmentioning
confidence: 60%
“…3 A study on ulnocarpal impaction found no difference in static ulnar variance between the symptomatic and contralateral wrist. 19 Static ulnar variance had no influence on the clinical results in our sample.…”
Section: Discussionmentioning
confidence: 60%
“…The Wafer technique described by Feldon is an open surgery procedure with a dorsal approach and resection of a 2to 3-mm lamina of the distal ulna. [33][34][35] Most hand surgeons now prefer to perform the Wafer technique arthroscopically, both in stage 2B, with a degenerated and thinned central portion of the TFC, and 2C, with central perforation of the TFC, due to arthroscopy's less aggressive nature and better functional results. This procedure consists of debridement of the central portion of the TFCC and resection through the defect of a small segment of the ulnar dome (►Fig.…”
Section: Degenerative Tfcc Injuries (Palmer Class 2)mentioning
confidence: 99%
“…6). [33][34][35] The different techniques of distal ulna resection arthroplasty and prosthesis are usually evaluated with conventional radiographs that make possible the assessment of the resection performed, the placement of the prostheses, the alignment of the bone structures, and the stability of the DRUJ. 5,6 Complications Surgical techniques used to treat the different lesions of the TFCC present general complications common to any surgical procedure, such as arthrofibrosis, infection, or complex regional pain syndrome.…”
Section: Normal Postoperative Appearancementioning
confidence: 99%
See 1 more Smart Citation
“…The more positive the UV (less negative), the smaller the coronal length of the SN (from the inferior edge of the SN proximally to where it meets the ulnar articular surface of the lunate facet distally) [1]. The UV has also been shown to have a dynamic component and has been found to increase with grip [7].…”
Section: Osseous Anatomy and Biomechanicsmentioning
confidence: 99%